2019
DOI: 10.1101/533141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extinction-resistant attention to long-term conditioned threat is indexed by selective visuocortical alpha suppression in humans

Abstract: 1 2 While ERP studies have shown heightened early visual attention to conditioned threat, it is unknown 3 whether this attentional prioritization is sustained throughout later processing stages and whether it is 4 robust to extinction. To investigate sustained visual attention, we assessed visuocortical alpha 5 suppression in response to conditioned and extinguished threat. We reanalysed data from N = 87 male 6 participants that had shown successful long-term threat conditioning and extinction in self report… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
2
10
0
Order By: Relevance
“…Supporting this interpretation, a previous study found the adaptation of limbic brain areas to be accompanied by increased engagement of visual cortex during fear conditioning ( Lithari et al , 2016 ). Such persistent visuocortical engagement with the threat cue may be particularly adaptive in conditioning regimes with intermittent pairing, in which not all CS+ trials include a US presentation, promoting exploration behavior and scanning of the environment for contingency cues—a hypothesis that is readily testable in future research and consistent with extinction-resistant alpha power changes during a 2-day conditioning regimen ( Panitz et al , 2019 ). Notably, heightened attention to the threat cue is unlikely to explain the cross-species observation that extensive conditioning over time prompts selectively heightened visuocortical responses at very short latencies and in retinotopic visual areas.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this interpretation, a previous study found the adaptation of limbic brain areas to be accompanied by increased engagement of visual cortex during fear conditioning ( Lithari et al , 2016 ). Such persistent visuocortical engagement with the threat cue may be particularly adaptive in conditioning regimes with intermittent pairing, in which not all CS+ trials include a US presentation, promoting exploration behavior and scanning of the environment for contingency cues—a hypothesis that is readily testable in future research and consistent with extinction-resistant alpha power changes during a 2-day conditioning regimen ( Panitz et al , 2019 ). Notably, heightened attention to the threat cue is unlikely to explain the cross-species observation that extensive conditioning over time prompts selectively heightened visuocortical responses at very short latencies and in retinotopic visual areas.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha blocking has been shown to correlate with enhanced cortical processing of low-level stimulus properties such as color and motion when these dimensions are made task-relevant (Snyder & Foxe, 2010), and here we demonstrate that the alpha-band response is also sensitive to SF-associated contingencies. In addition, although alpha suppression in response to naturally foreboding stimuli is well established (e.g., Vagnoni, Lourenco, & Longo, 2015;De Cesarei & Codispoti, 2011;Huster, Stevens, Gerlach, & Rist, 2009;Güntekin & Basar, 2007), only recently (Panitz, Keil, & Mueller, 2019) has this effect been linked to conditioned threat cues. The present work shows that conditioned alpha blocking extends to a visual feature as basic as spatial frequency when such information provides the only basis for discriminating threatening from nonthreatening stimuli.…”
Section: Alpha Powermentioning
confidence: 99%
“…However, there has been limited empirical research on alpha-band suppression during aversive conditioning ( Chien et al. , 2017 ; Panitz et al. , 2019 ; Friedl and Keil, 2020 , 2021 ; Yin et al.…”
Section: Introductionmentioning
confidence: 99%